Growth Traits and Yield Performance of Japonica Hybrid Rice Bred by the New Strategy in the Yangtze River Region of China - Yutiao Chen; Jiayu Song; Xiaofu Hong; Huaijie Zhang; Tiejun Hu; Guanglong Zhu (Agronomy)
Despite the successful breeding of hybrid japonica rice by the new strategy (the female parent with a restorer line containing an appropriate proportion of indica rice genes) in China, it remains unclear whether these cultivars exhibit a similar yield performance with the traditional high-yield hybrid cultivars in the Yangtze River region. Therefore, two field experiments were conducted in Fenghua City and Yuyao City, China, during the two growing seasons in 2019 and 2020. Six japonica hybrid rice cultivars and one control indica–japonica hybrid rice cultivar (Yongyou1540 [YY1540]) were chosen as the experimental materials in each year, and the seedling quality, grain yield, and yield components were evaluated. The results showed that the grain yield of YY1540 was 13.9 t ha−1 and 14.5 t ha−1 in 2019 and 2020, respectively, which was the highest among all cultivars in both years. However, the japonica hybrid rice cultivars CHY83 in 2019 and CHY112 in 2020 also achieved high yield performance with 13.7 t ha−1 and 14.0 t ha−1, respectively, which were not significantly difference from YY1540. The japonica hybrid cultivars with a high grain yield typically exhibited more spikelets per panicle, more spikelets per m2, and a higher harvest index than those with a lower grain yield. Increasing the total growth duration had a limited impact on the grain yield of japonica hybrid rice. However, the post-heading daily grain yield was significantly positively correlated with grain yield in japonica hybrid rice cultivars. Moreover, significant quadratic relationships were observed between plant height at maturity and grain yield and between seedling dry weight and grain yield. The optimal plant height at maturity and seedling dry weight for achieving a high grain yield in japonica hybrid rice were approximately 130 cm and 300 mg plant−1, respectively. This study provides useful information for breeding high-yield japonica hybrid cultivars.